Functional Antecedent of Corporate Reputation in Universities: Developing A Measurement Tool for the Corporate Reputation Attributes (CRA) - Bilginer, Gizem; Süral Özer, Pınar (International Journal of Contemporary Economics and Administrative Sciences, 2023)
It is important for universities seeking to gain a competitive advantage to focus on reputation management like all other institutions. At this point, although university rankings are helpful, each university's management of its reputation by positioning itself according to its unique characteristics will yield more effective results. The Reputation Quotient (RQ) Scale, which is frequently used in the literature for measurement, complicates the understanding of reputation by considering the antecedents of reputation together with the structure itself. RQ has been updated as the RepTrak System Model to separate them: RepTrak Pulse covers the measurement of emotion-based pure reputation perception, and RepTrak Index covers the measurement of reputation antecedents. Although emotions are universal, the assumption that reputation-determining driving attributes do not differ across cultures and contexts is problematic. The main objective of the present study is to develop a measurement tool for 'corporate functions and attributes', one of the experience areas that are considered critical in the formation of corporate reputation perceptions in Turkish state universities. The study was carried out with the exploratory sequential mixed-method design. In the first study, the experience areas that determine the reputation perceptions of the academicians were revealed, while the second study focused on developing a context-specific measurement tool. The Corporate Reputation Attributes Scale consists of five dimensions including Working Environment and Governance, Research and Education Capacity, Social Awareness, Innovation and Social Networking and Recognition, and 24 items. It is recommended that universities include corporate reputation management in their priority areas in their strategic plans, and that they base their strategies on current situation analyzes that they will carry out with measurement tools such as CORPORATE REPUTATION ATTRIBUTES (CRA).